Structural and optical properties of neodymium doped magnesium lithium tellurite glass embedded with silver nanoparticles - Nur Ashiha Azmi, 1990- author; Md. Rahim Sahar, supervisor; Sib Krishna Ghoshal, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014